Application of the nourseothricin acetyltransferase gene (nat1) as dominant marker for the transformation of filamentous fungi - Ulrich Kück; Birgit Hoff (Fungal Genetics Reports, 2006)
Here, we report the construction of two transformation vectors, pD-NAT1 and pG-NAT1, carrying the nat1 gene encoding the nourseothricin acetyltransferase. The nat1 gene is expressed under the control of the Aspergillus nidulans trpC promoter and thus can be used as a dominant drug-resistance marker for the DNA-mediated transformation of filamentous fungi. The successful application of both vectors was demonstrated by transforming the homothallic ascomycete Sordaria macrospora as well as the β-lactam producerAcremonium chrysogenum. For both fungi and for both vectors, transformation frequencies were between 10 and 40 transformants per 10 µg of plasmid DNA.